The record-breaking precipitation event of December 2022 in Portugal - T. M. Ferreira; T. M. Ferreira; R. M. Trigo; T. H. Gaspar; J. G. Pinto; A. M. Ramos (Natural Hazards and Earth System Sciences)
Extreme precipitation events (EPEs) potentially present an enormous societal risk and often lead to major human and economic impacts. In the mid-latitudes, such EPEs are often triggered by intense extratropical cyclones and their associated frontal systems. Over the last decade, several studies have shown the important and specific role played by atmospheric rivers (ARs) in the occurrence of EPEs in western Europe, particularly in the Iberia Peninsula. In this study we analyze the all-time 24 h record-breaking precipitation (120.3 mm) recorded in the historical Dom Luiz Observatory (records since 1863) in Lisbon, Portugal, between 12 and 13 December 2022. A synoptic evaluation of surface and upper-level fields from 5 to 14 December is performed using the European Centre for Medium-Range Forecasts (ECMWF) Reanalysis v5 (ERA5). The week before the EPE, there was a combined effect of a large-scale sea-level-pressure (SLP) gradient resembling the North Atlantic Oscillation (NAO) negative phase, a southerly position of the jet stream, and above-normal positive sea surface temperature (SST) anomalies over the North Atlantic that led to the development of several low-pressure systems at relatively low latitudes, all traveling along the same mean path towards western Europe. The atmospheric river associated with this event was first detected late on 10 December, associated with a deep extratropical cyclone. The combination of high integrated vapor transport (and moisture inflow by the warm conveyor belt), with a dynamical component characterized by a suitable uplift motion allowed the system to evolve and maintain its AR characteristics for 72 h. The extratropical cyclone and associated AR moved northeast towards Iberia, making landfall in Portugal on 12 December as an extreme AR event, leading to the 24 h record-breaking precipitation event.